2014
DOI: 10.1177/0268355514555547
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser ablation with and without high ligation compared to high ligation and stripping for treatment of great saphenous varicose veins: Results of a multicentre randomised controlled trial with up to 6 years follow-up

Abstract: Clinical recurrence appears with the same frequency in all three treatment groups, but the responsible pathological mechanisms seem to differ. Most reflux into the great saphenous vein and side branches appears after endovenous laser ablation, whereas more saphenofemoral junction-independent recurrences are seen after high ligation/stripping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 23 publications
2
51
0
7
Order By: Relevance
“…Rasmussen and colleagues reported the 3‐year follow‐up of a RCT comparing four different GSV treatments (conventional surgery with local tumescent anaesthesia, EVLA, radiofrequency ablation and UGFS, all with concomitant phlebectomies) and observed no differences between the four groups in Venous Clinical Severity Score and quality of life; nor was there a difference in the incidence and anatomical location of recurrent tributaries. Recently, a RCT comparing conventional surgery, EVLA with high ligation, and EVLA without high ligation confirmed that clinical recurrence did not differ between the three treatment groups up to 6 years after treatment. It is clear that, irrespective of the technique employed to treat varicose veins, progression of disease cannot be stopped in the long term.…”
Section: Discussionmentioning
confidence: 97%
“…Rasmussen and colleagues reported the 3‐year follow‐up of a RCT comparing four different GSV treatments (conventional surgery with local tumescent anaesthesia, EVLA, radiofrequency ablation and UGFS, all with concomitant phlebectomies) and observed no differences between the four groups in Venous Clinical Severity Score and quality of life; nor was there a difference in the incidence and anatomical location of recurrent tributaries. Recently, a RCT comparing conventional surgery, EVLA with high ligation, and EVLA without high ligation confirmed that clinical recurrence did not differ between the three treatment groups up to 6 years after treatment. It is clear that, irrespective of the technique employed to treat varicose veins, progression of disease cannot be stopped in the long term.…”
Section: Discussionmentioning
confidence: 97%
“…These differences have implications for the need for retreatment. Longer‐term data from randomized clinical trials (RCTs) and cohort studies, after an average of 5 years of follow‐up, suggest that these differences seem to increase over time.…”
mentioning
confidence: 99%
“…There were 11 articles comprising a total sampling size of 1145 patients with lower limb varicosity meeting all inclusion and exclusion criteria, and then were included in this meta‐analysis. The sample sizes of these studies vary from 40 to 173.…”
Section: Resultsmentioning
confidence: 99%